A Study of Fatigue Behavior of Beam Column Joint Under Moderate Earthquake Loading - Muhammad Khairul Amri bin Mahat, Muhammad Khairul Amri (Universiti Teknologi Petronas, 2009)
On 26 December 2004. Malaysia was affected by the Indian Ocean earthquake. Despite its proximity to the epicenter of the earthquake, Malaysia escaped the kind of damage that struck countries thousands of miles further away. Since the epicenter was on the western coast of Sumatra, the island largely shielded the country from the worst of the tsunami. Structures and buildings in Malaysia are design in accordance to British Standard (BS) which neglect seismic loading. This research aims to estimate the fatigue life of reinforced concrete beam-column joint under moderate earthquake loading. A case study is chosen base on existing structure which is a school. Lightly reinforced concrete beam-column joint is selected and 5 samples were constructed. Samples are put under seismic loading and investigations on load and deflection were conducted. Theoretical study was conducted using STAAD Pro by modeling the whole structure undergoing seismic load in the form of time-history data, obtained from Siukuai Island, Indonesia. The result of displacement response is later used to calculate the stress of structure during earthquake. It was observed that the maximum displacement of the structure under the earthquake load is 5.45 mm, while the fatigue damage of the structure due to the equivalent cyclic loading is 28%. Hence, a structure in Malaysia undergone an earthquake with VI MMI will have 72% of fatigue Iife remaining.